Hierarchical regulation of NADPH oxidase by protein kinases in plant immunity. (July 2016) - Yoshioka, Hirofumi; Adachi, Hiroaki; Nakano, Takaaki; Miyagawa, Noriko; Asai, Shuta; Ishihama, Nobuaki; Yoshioka, Miki
Abstract: Plant immune responses are attributable to hierarchical immunities, pattern-triggered immunity (PTI) and effector-triggered immunity (ETI). The plant NADPH oxidase, RBOH, is a major player in the pathogen-responsive reactive oxygen species (ROS) burst. Nicotiana benthamiana RBOHB is responsible for both the transient PTI ROS burst and the robust ETI ROS burst. Our understanding of the activation mechanisms controlling RBOH during PTI and ETI has increased in recent years. MAPKs are involved in the ETI ROS burst by transactivation of NbRBOHB, but not in the PTI ROS burst. We also introduce mechanisms of RBOH regulation at the post-transcriptional level by diverse protein kinases. Highlights: The plant NADPH oxidase, RBOH, plays a pivotal role in the immune ROS burst. CDPKs, RLCKs and CBL/CIPK activate RBOH by direct phosphorylation. MAPKs induce transactivation of RBOH in response to ETI signals. RBOH is regulated at the post-transcriptional level by diverse protein kinases.